Determinants of Capital Structure: Empirical Evidence From UK - XU, WENJING (2010)
This paper investigates the determinants of capital structure for the companies in the United Kingdom. The aim of this study is to determine which capital structure is more appropriate to UK listed companies. Results obtained will be compared against previous empirical and theoretical predictions. Panel data set containing 342 UK public quoted companies across 8 industries during the period from 2000-2009 is employed. A Pooled OLS regression is constructed to discuss what the determinants of a firm’s leverage are and how these determinants will affect the capital structure decisions. The impact of industry classification is also taken into considertion. The industries are introduced as dummy variables in the analysis. Each of the regressions uses Total, Long-Term Leverage and Short-Term Leverage as dependent variables. Firm Size, Profitability, Asset Tangibility, Growth Opportunities and Non-Debt Tax Shields are selected as independent variables .